The Job Satisfaction of Finnish Nursing Staff: The Development of a Job Satisfaction Scale and Survey Results. (23rd October 2012) - Kvist, Tarja; Mäntynen, Raija; Partanen, Pirjo; Turunen, Hannele; Miettinen, Merja; Vehviläinen-Julkunen, Katri
Abstract : This paper describes the development of the Kuopio University Hospital Job Satisfaction Scale (KUHJSS) and the results of the survey. The scale was developed through a systematic literature review, and its validity and reliability were assessed using several psychometric properties including expert evaluation (n = 5 ), a pilot survey (n = 172 ), and exploratory factor analysis. The final version of KUHJSS included 37 items. A large sample psychometric evaluation was made by nursing staff (n = 2708 ). The exploratory factor analysis revealed seven factors with modest internal consistency (0.64–0.92). The staff reported relatively high job satisfaction. The greatest satisfaction was derived from motivating factors associated with the work; the least, from the job's demands. Respondents who considered their working units to provide an excellent quality of care reported the highest job satisfaction in every subarea (P < .0001 ). The KUHJSS proved to be a reliable and valid tool for measuring job satisfaction in hospital care.